Evaluation of hyperreflective foci as a prognostic factor of visual outcome in retinal vein occlusion - Bin Mo; Hai-Ying Zhou; Xuan Jiao; Feng Zhang (International Journal of Ophthalmology, 2017)
AIM: To evaluate the potential role of hyperreflective foci (HF) as a prognostic indicator of visual outcome in patients with macular edema (ME) due to retinal vein occlusion (RVO). METHODS: We retrospectively reviewed 50 eyes of 50 patients with ME due to ischemic central retinal vein occlusion (CRVO), non-ischemic CRVO and branch retinal vein occlusion (BRVO) who were treated with anti-vascular endothelial growth factor (anti-VEGF) at Beijing Tongren Eye Center from January 2013 to July 2016. All patients underwent best-corrected visual acuity (BCVA), spectral domain optical coherence tomography (SD-OCT) at baseline and follow-up. Such factors were evaluated and compared among three groups as baseline and final BCVA, central retinal thickness (CRT), external limiting membrane (ELM) status and the numbers of HF in different position. Multiple linear regression analysis was employed to analyze the relationship between baseline HF and final BCVA. Changes of HF before and after treatment were evaluated too. RESULTS: Among three groups, HF could be located in each retinal layers, as well as in vitreous cavity. The mean HF in outer retinal layer (ORL) at baseline was 5.29±8.48 in ischemic CRVO with intact ELM, 1.93±2.76 in non-ischemic CRVO, and 1.75±2.05 in BRVO. With disrupted ELM, the mean HF in ORL increased. There was statistically difference of HF in ORL between intact and disrupted ELM. The numbers of HF in ORL were associated with poor visual outcome among three groups. However, HF in inner retinal layer (IRL) and vitreous cavity were not associated with poor visual outcome. Meanwhile, the baseline HF in ORL and vitreous cavity reduced significantly in non-ischemic CRVO and BRVO after anti-VEGF treatment. CONCLUSION: The numbers of HF in ORL are prognostic factors associated with the final BCVA in patients with ME due to RVO after anti-VEGF treatment.